The Effectiveness of Using Snake and Ladder Game in Vocabulary Mastery of seventh-grade students at SMPN 1 Sikur - Maulinda, Maulinda; Fikni, Zahratul; Prasetyaningrum, Ari; Husnu, Muhammad (Journal of English Language and Education, 2025)
This study aims at investigating the effectiveness of the Snake and Ladder game as a learning medium to improve English vocabulary mastery among seventh-grade students at SMPN 1 Sikur during the 2025/2026 academic year. A quantitative approach with experimental design was employed, involving an experimental group that used the Snake and Ladder game and a control group that received conventional instruction. The type of test that used in the study was multiple choice, consist of 20 items, was administered both before and after the treatment. The experimental group’s mean score improved from 63.97 to 83.79, while the control group’s mean score increased from 66.24 to 80.41. A t-test yielded a significance value of 0.01, indicating that the difference between groups was statistically significant. These results demonstrate that the Snake and Ladder game is effective in enhancing students’ vocabulary mastery. Furthermore, the study suggests that integrating educational games into language teaching can make learning more engaging, increase student motivation, and foster active participation.